Urinary Dysfunction Is Associated with Nigrostriatal Dopaminergic Degeneration in Early and Untreated Patients with Parkinson’s Disease - Jing Wang; Ruihua Cao; Tao Huang; Cheng Liu; Yidong Fan (Parkinson's Disease)
The aim of the present study was to determine the relation between urinary dysfunction and nigrostriatal dopaminergic degeneration in early and untreated Parkinson’s disease (PD). The data were obtained from Parkinson’s Progression Markers Initiative database. Two hundred and seventy-five patients and 149 healthy controls were included in our analysis. Urinary symptoms were evaluated with the Scale for Outcomes in Parkinson’s Disease for Autonomic Symptoms (SCOPA-AUT). We performed correlation analyses between 123I-FP-CIT SPECT imaging data and severity of urinary symptoms in patients with PD and healthy controls. Early and untreated patients with PD exhibited worse urinary symptoms when compared with healthy controls. The severity of urinary symptoms significantly correlated with dopamine transporter binding levels in the caudate and the putamen. After controlling for age and sex, the severity of storage symptoms significantly correlated with dopamine transporter binding levels in the less affected side of the putamen (r = −0.172, p=0.004). The correlation was observed in both male (r = −0.152, p=0.043) and female patients (r = −0.217, p=0.034). No correlations were found between dopamine transporter binding levels and voiding symptoms in male or female patients, or any urinary symptoms in healthy controls. Worse storage symptoms reflect greater nigrostriatal dopaminergic loss in early and untreated PD.